2000
DOI: 10.1029/2000jd900144
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lidar observations of Arctic polar stratospheric clouds during January 1989

Abstract: Abstract. We present analyses of lidar backscatter and depolarization ratios for polar stratospheric clouds (PSCs) observed during the 1989 Airborne Arctic Stratospheric Experiment. The backscatter and depolarization ratios are available at one visible and one infrared wavelength. Water ice PSCs were identified at low ambient temperatures based upon their relatively large backscattering and depolarization ratios. The remaining clouds fall into four major categories. First, we observe a class of clouds that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
124
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 80 publications
7
124
0
Order By: Relevance
“…More recent studies (e.g., Gobbi et al, 1998;Toon et al, 2000;Biele et al, 2001;Hu et al, 2002;Adriani et al, 2004;Massoli et al, 2006) indicate that such distinct "typing" of PSCs is an oversimplification, with the clouds often occurring as mixtures of liquid and solid particles. Hence, we explore the CALIOP measurement space using a theoretical optical model for simple notional mixtures of STS and NAT or ice particles, and then use these calculations in conjunction with statistical analyses of the CALIOP aerosol depolarization data to define new CALIPSO-based PSC composition classes.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies (e.g., Gobbi et al, 1998;Toon et al, 2000;Biele et al, 2001;Hu et al, 2002;Adriani et al, 2004;Massoli et al, 2006) indicate that such distinct "typing" of PSCs is an oversimplification, with the clouds often occurring as mixtures of liquid and solid particles. Hence, we explore the CALIOP measurement space using a theoretical optical model for simple notional mixtures of STS and NAT or ice particles, and then use these calculations in conjunction with statistical analyses of the CALIOP aerosol depolarization data to define new CALIPSO-based PSC composition classes.…”
Section: Introductionmentioning
confidence: 99%
“…Trajectory studies reveal that the physical state of sulfate particles and PSCs in the stratosphere is strongly controlled by the temperature history of the air mass (e.g. Tabazadeh et al, 1995;Larsen et al, 1997;Toon et al, 2000). Type Ib PSCs are composed of supercooled ternary solution particles (STS; H 2 SO 4 /H 2 O/HNO 3 ) and are formed by the uptake of H 2 O and HNO 3 on the liquid stratospheric H 2 SO 4 /H 2 O (background) aerosols at temperatures below ≈193 K (Carslaw et al, 1994;Meilinger et al, 1995;Peter, 1997;Lowe and MacKenzie, 2008).…”
mentioning
confidence: 99%
“…Besides the exact formation mechanism of PSC type Ia and II, it seems that temperatures below T ice for PSC type Ia formation are not necessarily required (e.g. Toon et al, 2000;Drdla and Browell, 2004). In general, homogeneous formation processes have been assumed, but measurements have indicated that solid PSC particles can also be formed heterogeneously (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…varies in a nonlinear way as particle size increases (Toon et al 2000;Brooks et al 2004). Trends in depolarization with optical diameter also depend on the aspect ratio of the particles (Brooks et al 2004).…”
Section: Optical Properties Of Ice Crystals and Ice Nucleimentioning
confidence: 99%